Copatching and Lipid Raft Association of Different Viral Glycoproteins Expressed on the Surfaces of Pseudorabies Virus-Infected Cells - Favoreel, Herman W. (American Society for Microbiology, 2004)
Pseudorabies virus (PRV) is a swine alphaherpesvirus that is closely related to human herpes simplex virus (HSV). Both PRV and HSV express a variety of viral envelope glycoproteins in the plasma membranes of infected cells. Here we show that at least four major PRV glycoproteins (gB, gC, gD, and gE) in the plasma membrane of infected swine kidney cells and monocytes seem to be linked, since monospecific antibody-induced patching of any one of these proteins results in copatching of the others. Further, for all four PRV glycoproteins, monospecific antibody-induced patches were enriched in GM1, a typical marker of lipid raft microdomains, but were excluded for transferrin receptor, a nonraft marker, suggesting that these viral proteins may associate with lipid rafts. However, only gB and, to a lesser extent, gE were found in lipid raft fractions by using detergent floatation assays, indicating that gC and gD do not show strong lipid raft association. Addition of methyl-β-cyclodextrin (MCD), a cholesterol-depleting agent that is commonly used to disrupt lipid rafts, only slightly reduced copatching efficiency between the different viral proteins, indicating that other factors, perhaps tegument-glycoprotein interactions, may be important for the observed copatching events. On the other hand, MCD strongly reduced polarization of the antibody-induced viral glycoprotein patches to a cap structure, a gE-dependent process that has been described for specific PRV- and HSV-infected cells. Therefore, we hypothesize that efficient gE-mediated capping of antibody-antigen patches may require the lipid raft-associated signal transduction machinery.